Improving the Reading and Writing Performance of a Student with Dyslexia: An Action Research Study - Balantekin, Yakup (International Electronic Journal of Elementary Education, 2022)
In this study, it was aimed to improve the reading and writing performance and reading motivation of a third grade primary school student without any cognitive and physical disabilities. In the study conducted by action research method, one of the qualitative research methods, the student's reading and writing performance and reading motivation were evaluated by scales. While fluent reading strategies were used to improve the student's reading performance, the strategy of identifying the main idea at the sentence level was used to improve reading comprehension skills. The programmed instruction approach was adopted to improve students' writing skills. At the end of the study, there was an improvement in the student's word recognition level, reading speed, comprehension percentage and reading motivation. While planning the support programs for students with reading and writing problems, it has been recommended that it is necessary to decide to develop both skills together or only one skill by considering the intensity of the student's needs and that reading books prepared for students should consist of stories long enough to end in one reading.